ANALISIS KINERJA KEUANGAN TERHADAP RETURN SAHAM PADA SEKTOR PERBANKAN SEBELUM DAN SELAMA PANDEMI COVID-19 - Lilia Valentina (Media Akuntansi dan Perpajakan Indonesia, 2023)
This study aims to determine the effect of ROA and ROE on stock returns. The population of this research is banking companies listed on the Stock Exchange during the 2019 and 2020 period. The sampling technique used is purposive sampling technique. The type of data used is secondary data. The sample that was obtained based on the criteria are 7 banks. The data technique used is multiple linear regression analysis. The result of this study indicates that ROA dan ROE has no significant effect on stock return.